Determinación de las competencias organizacionales en las empresas agroproductivas procesadoras de plátano y banano de la zona norte de Manabí - Chávez Loor, Wendy Tatiana (2020)
The present investigation was carried out in the northern zone of Manabí and its objective was to establish the organizational competencies in the agro-productive companies that process plantains and bananas. We proceeded from what was recommended by Bravo (2018), starting with a field investigation to obtain the characterization matrix, subsequently applying hierarchical clusters, from which representative samples were taken. Through the method of experts, an identification of the organizational competencies was carried out, which were evaluated with the method proposed by Alles (2014), applying the evaluation form and intangible indicators, obtaining the gaps of the organizational competencies. Through an interview with the managers, the strategy was aligned with the organizational competencies in the recruitment manual. With the inductive and deductive methods, the following conclusions were established: 91% of the companies investigated are owned by natural people, whose staff is made up of 82% men. 10 organizational competencies were considered. In the evaluation, gaps were detected, especially in skills such as innovation. Organizational competencies such as respect, commitment, responsibility and ethics are in grade A. In competencies such as leadership, teamwork, effective communication, initiative, there are significant gaps. Between 90 and 95% have primary or secondary training, so in the manual's preparation and recruitment profiles, level B should be considered in the degree of organizational competencies at the operative levels.